Track Files with Characteristics and Accompanying Atmospheric Data for Long Track Tropopause Polar Vortices from 1979-2018 ... - Bray, Matthew; Cavallo, Steven (NSF Arctic Data Center, 2025)
Tropopause polar vortices (TPVs) are closed circulations centered on the tropopause that form and predominately reside in high latitudes. Due to their attendant flow, TPVs have been shown to influence surface weather features, and thus, a greater understanding of the dynamics of these features may improve our ability to forecast impactful weather events. These data include a subset of TPVs that have lifetimes of longer than two weeks (the 95th percentile of all TPV cases between 1979 and 2018); these long-lived vortices offer a unique opportunity to study the conditions under which TPVs strengthen and analyze patterns of vortex formation and movement. These data use ERA-Interim, along with TPV tracks derived from the same reanalysis, including data on the formation, motion, and development of these long-lived vortices. Data also include long-lived TPVs that form predominately by splitting from existing vortices. Data from non-likely split genesis events are also included. Seasonal variations in the life ...